An Analysis of Culture Shock Faced by Dre Parker on Karate Kids 2010 Movie - Fatqu Rofiqoh Dewi, M.Pd (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2021)
Staying in the new environment makes the person feel pain if he/she does not know the culture of it. It is called culture shock. Culture shock is the feeling of disorientation experienced by someone who is suddenly subjected to an unfamiliar culture, way of life, or set of attitudes. It can happen when someone who stays in another place has different culture. Culture shock is negative thing because it can make the one who gets it feel confused, stressed, or depressed. The research analyzed the movie, which had culture shock situation as the story. The title of the movie was Karate Kids. Karate Kids movie told about the 12 years old boy, Dre Parker, who moved from Detriot U.S to Beijing China. He felt stressed because his new place was very different with his home before. The research is useful for the students who want to stay or move to new place with different culture for long time. The purposes of the research were to know what culture shock is faced by Dre Parker in Karate Kids Movie, to know how Dre Parker solved the problem, to give the beneficial information for the students who read this research. The method used by the researcher was qualitative research with observation and documentation as the instruments. The results of the research were based on Winkelman’s theory. There were four stages in culture shock. Those were the honeymoon or tourist phase, the crises phase, the adjustment and reorientation phase, and the adaptation; resolution; or acculturation stage. Keywords: Culture, Culture Shock, Movie